Life Satisfaction of Employees, Labour Market Tightness and Matching Efficiency - Pablo de Pedraza; Martin Guzi; Kea Tijdens (Masaryk University, Faculty of Economics and Administration, 2020)
Di Tella et al. (2001) show that temporary fluctuations in life satisfaction (LS) are correlated with macroeconomic circumstances such as gross domestic product, unemployment, and inflation. In this paper, we bring attention to labour market measures from search and matching models (Pissarides 2000). Our analysis follows the two-stage estimation strategy used in Di Tella et al. (2001) to explore sectoral unemployment levels, labour market tightness, and matching efficiency as LS determinants. In the first stage, we use a large sample of individual data collected from a continuous web survey during the 2007-2014 period in the Netherlands to obtain regression-adjusted measures of LS by quarter and economic sector. In the second-stage, we regress LS measures against the unemployment level, labour market tightness, and matching efficiency. Our results are threefold. First, the negative link between unemployment and an employee's LS is confirmed at the sectoral level. Second, labour market tightness, measured as the number of vacancies per job-seeker rather than the number of vacancies per unemployed, is shown to be relevant to the LS of workers. Third, labour market matching efficiency affects the LS of workers differently when they are less satisfied with their job and in temporary employment. Our results give support to government interventions aimed at activating demand for labour, improving the matching of job-seekers to vacant jobs, and reducing information frictions by supporting match-making technologies.
Keywords: E24; J21; 330; life satisfaction; matching efficiency; tightness; unemployment